(1246) Advanced Mathematical treatment of least squares in economic applications المعالجة الرياضية المتقدمة للمربعات الصغرى في التطبيقات الاقتصادية - Omar, Amani; Hanna, Magdy Tawfik (The Institute Of National Planning., 2018)
Economic theory typically specifies exact functional relationships among its variables which do not hold in reality. A main task of econometric theory, indeed, is to provide a bridge between the exact relationships of economic theory and the disturb rlationships of economic reality.